Gender differences, UV exposure and risk of lentigo maligna in a nationwide healthcare population cohort study. (5th December 2018) - Higgins, H.W.; Cho, E.; Weinstock, M.A.; Li, T.Y.; Qureshi, A.; Li, W.Q.
Abstract: Background: Our understanding of the relationship between ultraviolet (UV) radiation exposure and lentigo maligna (LM) has been largely derived from epidemiologic/clinical studies based on invasive melanoma. Recent studies have shown gender differences in melanocytic tumours incidence. Objective: To examine the association of UV light with LM by gender remains unclear. Methods: Two prospective cohort study [Nurses' Health Study (1980–2012)] and [Health Professionals Follow‐up Study (1986–2010)] were analysed. All participants with LM or MIS, non‐LM type were included in analysis. UV index at birth, age 15, and age 30 were calculated by gender. Lifetime UV flux was calculated. Hazard ratios (HRs) were calculated. Results: A total of 110 485 women from NHS and 41 015 men from HPFS were examined. A total of 281 LM and 776 melanoma in situ (MIS), non‐LM cases were reported. Risk of LM increased with increasing UV flux exposure in multivariate‐adjusted models for men ( P for trend = 0.04), but not for women ( P for trend = 0.91). Conclusions: UV flux may be associated with LM in men but not in women.